RESEARCHES ABOUT MARRIAGES AND WEDDINGS OF KARAKALPAKS - Archeology Doshniyazov Rakhat (Web of Journals Publishing, 2023)
The article deals with the issue of Karakalpak marriage. Researches of Karakalpak wedding customs in classical literature are analyzed. The transformation steps of thick money and its types in Karakalpaks are shown. The uniqueness of weddings in the life of modern Karakalpaks, Novatian circumstances in customs and traditions is based on researched and collected materials.
Keywords: Karakalpaks, wedding, transformation, innovation, traditions, thick money.